TRAINING FUTURE TEACHERS OF COMPUTER SCIENCE FOR WORKING OUT TECHNOLOGICAL CARDS OF LESSONS IN THE CONDITIONS OF REALIZATION OF THE FEDERAL STATE EDUCATIONAL STANDARD FOR GENERAL EDUCATION - Kuvshinova, E.N. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
This article is devoted to a problem of readiness of future teachers of informatics for development of flow charts of the lessons displaying the main requirements of Federal state educational standards of the main general education (FGOS of Ltd company) to planning and the organization of educational process taking into account system and activity approach in training. Content of system and activity approach in training, the universal educational actions (UEA) reveals. Main units of the flow chart of a lesson of informatics are considered. The substantial block of the flow chart of a lesson of informatics determined by a training material which provides achievement of the planned subject results of training, and also forming and development of UUD, all-educational skills, ICT competences, competences of educational and research and project activities is stated.Subject results of training to which the abilities specific to a subject, types of activity on receipt of new knowledge within a subject, to its transformation and application in educational, educational and project and social and project situations, forming of scientific type of thinking, scientific ideas of key theories, types and types of the relations, ownership of scientific terminology, key concepts, methods and acceptances belong [10] are analyzed.Step-by-step training of future teachers of informatics for development of flow charts of lessons is discussed.